Supporting postgraduate taught students through tailored maths workshops and Q&A sessions - Richard, Morgiane (MSOR Connections, 2019)
Maths Support at the University of Aberdeen was established in 2012, and has been offered to all students, whatever their discipline and level. Early on, interest was raised amongst the Postgraduate population, which represents about 20% of the whole student population at the University of Aberdeen. Maths Support for Postgraduate students, however, will necessarily take different shapes to Maths Support for Undergraduates. Their time constraints are different; their timetable is often very full, with little opportunity to fit in potential extra sessions for Maths Support during the semester; they need to clarify their Maths queries early in order to be able to keep up with the pace of study. In addition, a significant proportion of Postgraduate students are mature students, coming back to studying a Master a number of years after completing their first degree, who may also be part-time, having to balance between study, work and family time. This paper will discuss the range of tailored Maths Support services developed at the University of Aberdeen for PGTs on Business, Engineering and Geosciences Masters programmes. Student and staff feedback on the usefulness of the service, gathered anecdotally, will also be presented.